2016
DOI: 10.1002/pbc.26325
|View full text |Cite
|
Sign up to set email alerts
|

A phase IIa study of afuresertib, an oral pan‐AKT inhibitor, in patients with Langerhans cell histiocytosis

Abstract: Afuresertib has clinical activity in some patients with newly diagnosed and advanced LCH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Notably, a recent report of a phase 2 clinical trial of pan-AKT inhibitor afuresertib for LCH patients, including 7 evaluable cases with pulmonary involvement, demonstrated that AKT inhibition exerts limited efficacy against pulmonary LCH patients. 54 Because AKT inhibition induces feedback activation of PI3K, 55 which could signal through AKT-independent downstream pathways, 56 AKT may not be an optimal target to suppress the PI3K pathway. Direct inhibition of PI3K isoform(s), rather than AKT inhibitors, would be warranted in future clinical trials for pulmonary LCH patients.…”
Section: Gr1mentioning
confidence: 99%
“…Notably, a recent report of a phase 2 clinical trial of pan-AKT inhibitor afuresertib for LCH patients, including 7 evaluable cases with pulmonary involvement, demonstrated that AKT inhibition exerts limited efficacy against pulmonary LCH patients. 54 Because AKT inhibition induces feedback activation of PI3K, 55 which could signal through AKT-independent downstream pathways, 56 AKT may not be an optimal target to suppress the PI3K pathway. Direct inhibition of PI3K isoform(s), rather than AKT inhibitors, would be warranted in future clinical trials for pulmonary LCH patients.…”
Section: Gr1mentioning
confidence: 99%
“…One year later, the patient presented with painful right‐sided neck swelling and a biopsy of the lesion confirmed recurrence of LCH. The patient was then treated with the oral pan‐AKT inhibitor afuresertib as part of a clinical trial . The patient responded to afuresertib therapy and completed a total of 30 weeks of treatment (Figure A).…”
Section: Case Descriptionmentioning
confidence: 99%
“…The patient was then treated with the oral pan-AKT inhibitor afuresertib as part of a clinical trial. 17 The patient responded to afuresertib therapy and completed a total of 30 weeks of treatment ( Figure 1A). Several months later, the patient relapsed and was treated with cytarabine 150 mg/m 2 /day for a 5-day course.…”
Section: Case Descriptionmentioning
confidence: 99%
“…In the trial presented in this issue, Arceci et al. report on afuresertib, an oral, potent, highly selective, reversible pan‐AKT inhibitor at 125 mg/day administered to adult treatment‐naïve (n = 7) or relapsing/refractory LCH patients (n = 10) . The majority of patients were treated for more than 24 weeks, with four patients receiving treatment for more than 48 weeks.…”
mentioning
confidence: 99%